2019
DOI: 10.1073/pnas.1815961116
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic CD8+T lymphocytes expressing ALS-causing SOD1 mutant selectively trigger death of spinal motoneurons

Abstract: SignificanceCD8+ T lymphocytes, which are typically devoted to eliminate malignant and infected cells, have been described in the central nervous system (CNS) of patients and mice with amyotrophic lateral sclerosis (ALS). However, their role in ALS pathogenesis has yet to be unraveled. Here, we show that ablation of CD8+ T cells in ALS mice increased the number of surviving motoneurons. CD8+ T cells expressing the ALS-causing superoxide dismutase-1 mutant protein recognize and selectively kill motoneurons in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 43 publications
6
76
1
Order By: Relevance
“…Collectively, our data and these cited studies suggest that intestinal flora can affect inflammatory outcomes in the spinal cord, which could influence neurodegenerative disease progression. In contrast to our results, the comprehensive microbiome study by Blacher et al did not find differences in the immune system of SOD1 G93A animals (Blacher et al, 2019), although it is a wellestablished hallmark of both SOD1 G93A animals and ALS patients (Thonhoff et al, 2018;Chiu et al, 2008Chiu et al, , 2009Engelhardt et al, 1993;Fiala et al, 2010;Gustafson et al, 2017;Murdock et al, 2016Murdock et al, , 2017Alexianu et al, 2001;Coque et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Collectively, our data and these cited studies suggest that intestinal flora can affect inflammatory outcomes in the spinal cord, which could influence neurodegenerative disease progression. In contrast to our results, the comprehensive microbiome study by Blacher et al did not find differences in the immune system of SOD1 G93A animals (Blacher et al, 2019), although it is a wellestablished hallmark of both SOD1 G93A animals and ALS patients (Thonhoff et al, 2018;Chiu et al, 2008Chiu et al, , 2009Engelhardt et al, 1993;Fiala et al, 2010;Gustafson et al, 2017;Murdock et al, 2016Murdock et al, , 2017Alexianu et al, 2001;Coque et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, CD8T cell expansion in the spinal cord is consistent with the literature in mice (Chiu et al, 2009) and human ALS patients (Engelhardt et al, 1993;Fiala et al, 2010). Recently, a report demonstrated that CD8T cells in SOD1 G93A mice may be selectively destroying motor neurons in ALS (Coque et al, 2019). The study also found that CD8T cells infiltrated to the spinal cord at 90 days onwards but displayed a distinct pattern of surface marker expression compared to peripheral CD8T cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Neuroin ammation caused by HSV-2 infection led to a pronounced increase of CD8 + T cells in the spinal cord, as shown by us here and by others (14). The viable fraction of the spinal cord CD8 + T cells in HSV-2 infected mice were CD44+ (and CD62L-) effector/memory cells, similar to what has been shown in other in ammatory diseases of the CNS (22) and in cell adhesion and migration to the CNS in general (23). The majority of the cells expressed granzyme B, and a few percent of them had recently degranulated.…”
Section: Discussionsupporting
confidence: 89%
“…Along this line, in a mouse model of tauopathy, CD8 cytotoxic T-cells directed against tau protein were shown to infiltrate the hippocampus and to drive cognitive alterations (9). Finally, besides AD and PD, several studies provided evidence that T-cells are activated during the course of Huntington's disease (HD), amyotrophic lateral sclerosis (ALS) and/or their animal models (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%